Tinjauan Pelaksanaan Contractor Safety Management System (CSMS) pada Proyek Insulation di Petrochina International Jabung Ltd. Geragai - Rizti, Mitha Pricilia; Aswin, Budi; Hubaybah, Hubaybah (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2023)
Contractors working on projects must have a CSMS to ensure their safety and health so that the work process runs smoothly. SKK Migas' 2016 sustainability report shows that by applying the CSMS method for contractors, the number of work accident victims in 2016 decreased by 33.8% from 2015. Therefore this study aims to analyze the description of the implemention of the Contractor Safety Management System (CSMS) Implementation At PetroChina International Jabung Ltd. Geragai By CV. Ekacipta Global Radian. Methods of The type of research used is descriptive qualitative. With K3 supervisor research informants Petrochina International Jabung Ltd, K3 manager CV. RGE, and employees of CV. RGE in the field. Data collection technique with In-depth Interview. Data analysis techniques with data reduction, data presentation, discussion of analysis and drawing conclusions. Commitment management at CV. RGE has been implemented properly and adequately. The CSMS program has been effective in accordance with its objectives and has led to targets set in terms of quantity, but in terms of quality it needs further improvement. Risk control has been implemented in the field where CV. RGE has created a JSA and inspected the site before work started well in advance. Safe behavior measures have also been implemented by CV. RGE by putting up K3 posters, holding safety meetings every morning before starting work, providing training to employees. Personal Protective Equipment (PPE) is also sufficient. Each employee receives his own PPE and is responsible for his PPE.